2011
DOI: 10.1371/journal.pone.0021829
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Effects on Timing: Attention versus Pacemaker Accounts

Abstract: Emotions change our perception of time. In the past, this has been attributed primarily to emotions speeding up an “internal clock” thereby increasing subjective time estimates. Here we probed this account using an S1/S2 temporal discrimination paradigm. Participants were presented with a stimulus (S1) followed by a brief delay and then a second stimulus (S2) and indicated whether S2 was shorter or longer in duration than S1. We manipulated participants' emotions by presenting a task-irrelevant picture followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 62 publications
6
79
1
Order By: Relevance
“…There is some evidence of differential effects of pleasant and unpleasant stimuli on timing and this evidence includes an underestimation effect for both pleasant (Gable & Poole, 2012) and unpleasant stimuli (Lui et al, 2011). The engagement of attentional processes is one explanation for these exceptions to the overestimation effect for arousing emotional stimuli: Perhaps under some circumstances individuals withdraw attention from unpleasant images and spend longer inspecting pleasant images (e.g., 'pleasure seeking').…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence of differential effects of pleasant and unpleasant stimuli on timing and this evidence includes an underestimation effect for both pleasant (Gable & Poole, 2012) and unpleasant stimuli (Lui et al, 2011). The engagement of attentional processes is one explanation for these exceptions to the overestimation effect for arousing emotional stimuli: Perhaps under some circumstances individuals withdraw attention from unpleasant images and spend longer inspecting pleasant images (e.g., 'pleasure seeking').…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the Fayolle et al (2015) study, however, the effects of reward were a fixed duration and did not increase proportionally with the durations being timed. As a consequence, the authors argued for an effect on attention that influences the saliency of a stimulus and how quickly participants start timing a signal rather than an arousal effect that influences clock speed throughout the trial (e.g., Folta-Schoofs et al, 2014;Lake et al, 2014, in press;Lui et al, 2011). In juxtaposition, the effects of footshock stress reported by Meck (1983) reflect a constant state of arousal because the electric shock was being delivered continuously, in a non-pulsed fashion during both training and testing sessions, but for different treatment groups in each phase of the experiment (see Fig.…”
Section: Effects Of Electric Shock On Interval Timingmentioning
confidence: 99%
“…Earlier closure of the attentional switch therefore increases the number of pulses included at the beginning of the stimulus duration, but this addition number of pulses staying the same (additive effect) whatever the total duration. Consequently, some researchers have surmised that attention processes contribute to the effects of negative, high-arousal emotion on time judgments, as threatening signals attract attention more quickly (Lui, Penney & Schirmer, 2011). For example, Lui et al (2011) showed that when individuals were shown an emotional picture from the IAPS just before the comparison duration, it captured their attention to the detriment of the timing of the subsequent signal.…”
Section: The Effect Of Negative High-arousal Emotion On Time Perceptionmentioning
confidence: 99%
“…Consequently, some researchers have surmised that attention processes contribute to the effects of negative, high-arousal emotion on time judgments, as threatening signals attract attention more quickly (Lui, Penney & Schirmer, 2011). For example, Lui et al (2011) showed that when individuals were shown an emotional picture from the IAPS just before the comparison duration, it captured their attention to the detriment of the timing of the subsequent signal. The problem is that threatening signals are assumed to both attract attention (faster orienting attention), and modulate the organism's arousal level.…”
Section: The Effect Of Negative High-arousal Emotion On Time Perceptionmentioning
confidence: 99%
“…Time estimation is based on the number of pulses accumulated, with more pulses leading to an increase in perceived duration. Arousal produces an overestimation of time due to an increase in the pacemaker's speed (Maricq, Roberts, & Church, 1981;Meck, 1983;Wearden & Penton-Voak, 1995; although see Lui, Penney, & Schirmer, 2011). In contrast, if attention to the task distracts from the processing of temporal information, this opens the switch and some pulses are lost.…”
Section: Introductionmentioning
confidence: 99%